2005
DOI: 10.3732/ajb.92.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Differences in growth trajectory and strategy of two sympatric congeneric species in an Indonesian floodplain forest

Abstract: Whole-plant development trajectories and sapling leaf displays were compared for two sympatric congeneric species, Pterospermum diversifolium and P. javanicum, in a tropical floodplain forest in East Kalimantan, Indonesia. We assessed their growth strategies and developed hypotheses for their coexistence within the community. Pterospermum diversifolium retains a monoaxial growth habit that promotes quick stem elongation; thus, it is taller when branches are initiated than is P. javanicum. The species differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…2), its stem diameter growth rate may be expected to result in greater stem elongation than in the other four species. Supposing that a species with wider A c has higher shade tolerance, since a wide crown can deploy many leaves with low degree of self-shading (Yamada et al 2000(Yamada et al , 2005a, the allometry between M and A c suggests that S. lancifolia, which attained widest A c with a given M, is the most shade-tolerant of the five species. This prediction needs to be verified by field data.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2), its stem diameter growth rate may be expected to result in greater stem elongation than in the other four species. Supposing that a species with wider A c has higher shade tolerance, since a wide crown can deploy many leaves with low degree of self-shading (Yamada et al 2000(Yamada et al , 2005a, the allometry between M and A c suggests that S. lancifolia, which attained widest A c with a given M, is the most shade-tolerant of the five species. This prediction needs to be verified by field data.…”
Section: Discussionmentioning
confidence: 97%
“…The adaptive significance of tree architecture has been assessed in terms of the values of these parameters (Kohyama 1987;King 1990; Kohyama and Hotta 1990;Turner et al 1995;Yamada et al 2000Yamada et al , 2005aYamada et al , 2006aSposito and Santos 2001). Although this approach would seem to oversimplify the complexity of a tree's architecture, it has nonetheless revealed many meaningful insights.…”
Section: Introductionmentioning
confidence: 99%
“…A branching growth habit could expand crown area more widely than a monoaxial growth habit, thereby distributing leaves more widely. Yamada et al (2005) compared the degree of self-shading within a crown between monoaxial and branched trees and showed that monoaxial trees that develop large leaves toward the apex of the stem had a larger degree of self-shading than branched trees. Therefore, branched trees have higher shade tolerance than monoaxial trees, if the branched and monoaxial trees have comparable photosynthetic capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Canopy trees branch less and put effort into achieving height growth to reach strong light (King 1990;Kohyama and Hotta 1990;King 1996). Yamada et al (2005) reported that two congeneric canopy tree species have different ontogenetic processes from the juvenile to mature stages, and they suggested that the species coexist by adopting different regeneration niches based on differing understory light conditions. Knowledge of how shoot development affects the growth and survival of plants is important to understanding coexistence mechanisms in diversified forests and would help explain the diversity of growth forms of rattans.…”
Section: Introductionmentioning
confidence: 98%
“…Many scientists accept that the different growth strategies of trees allow trees to coexist in the tropical rain forest under uneven light conditions (King 1990(King , 1996Kohyama and Hotta 1990;Yamada et al 2000Yamada et al , 2005Aiba and Nakashizuka 2005). Shrubs have a wide crown with frequent branching to maximize light interception in the relatively dark understory environment.…”
Section: Introductionmentioning
confidence: 99%